Increasing taxes after a financial crisis: Not a bad idea after all ... - Christos Koulovatianos; Dimitris Mavridis (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
Based on OECD evidence, equity/housing-price busts and credit crunches are followed by substantial increases in public consumption. These increases in unproductive public spending lead to increases in distortionary marginal taxes, a policy in sharp contrast with presumably optimal Keynesian fiscal stimulus after a crisis. Here we claim that this seemingly adverse policy selection is optimal under rational learning about the frequency of rare capital-value busts. Bayesian updating after a bust implies massive belief jumps toward pessimism, with investors and policymakers believing that busts will be arriving more frequently in the future. Lowering taxes would be as if trying to kick a sick horse in order to stand up and run, since pessimistic markets would be unwilling to invest enough under any temporarily generous tax regime.
urn:nbn:de:hebis:30:3-480455
Keywords: H30; D83; C11; D90; E21; D81; C61; 330; Bayesian learning; controlled diffusions and jump processes; learning about jumps; Gamma distribution; rational learning